Evaluation of Color and Translucency of Stained and Glazed Monolithic Lithium Disilicates and Zirconia After Toothbrushing with Different Dentifrices and Thermocycling - Mascaro, Bruno Arruda [UNESP]; Salomon, Jean-Pierre [UNESP]; Demartine, Marina Santos [UNESP]; Nicola, Tassiane Caroline [UNESP]; Reis, José Maurício dos Santos Nunes [UNESP] (Quintessence Publishing, 2024)
Purpose: To evaluate changes in color and translucency of stained and glazed monolithic lithium disilicates and zirconia after toothbrushing with conventional or whitening dentifrices followed by thermocycling. Materials and Methods: Samples (n = 20/material) from CAD/CAM (IPS e.max CAD [EC]) and pressable (IPS e.max Press [EP]) lithium disilicates and 5Y-PSZ zirconia (Prettau 4 Anterior [PA]) were prepared and received staining and glazing procedures. Aging was performed by toothbrushing with conventional (n = 10) or whitening (n = 10) dentifrices, followed by thermocycling simulating 5, 10, and 15 years. Color coordinates L*, a*, b*, and C* and hºvalues were assessed with a spectrophotometer at baseline and after each aging period to calculate color changes (ΔE00), lightness (ΔL*), and translucency parameter (TP). Data were analyzed using three-way repeated measures ANOVA’s followed by Sidak post-hoc test (α =.05). Results: When comparing the dentifrices, EC and EP produced the greatest ΔE00 after 15 years with the whitening dentifrice (P <.05). Regardless of the dentifrice, PA showed greater ΔE00 than EC after 10 years (P <.05). When comparing the aging periods, EC and PA did not show differences in ΔE00 for both dentifrices (P ≥.05). EC and EP produced an increased ΔL* after 15 years in the whitening group (P <.05). In the whitening groups, the ΔL* values of PA differ (P <.005) from those of lithium disilicates. Regardless of the experimental group, the TP values followed the inequality: PA < EC < EP (P <.05). Conclusions: Overall, the color of stained and glazed monolithic lithium disilicates and zirconia changed under aging with greater effects for whitening dentifrice. Aging did not influence translucency. Int J Prosthodont 2024;37:423–431. doi: 10.11607/ijp.8495